Habilidades sociales y desarrollo de la autoestima en niños de la Institución Educativa Inicial Jardin Piloto N° 179, Iquitos 2022 - Rodriguez Rios, Leydi Sharon (2024)
The research titled “Social skills and development of self-esteem in children of the Initial Educational Institution, Garden Piloto N° 179, Iquitos, 2022”, presents as a general research problem: How are social skills related to the development of self esteem in children? children of the Initial Educational Institution Garden Piloto N° 179 Iquitos 2022?, having as a research objective, determine the relationship of social skills and the development of self-esteem of children of the Initial Educational Institution Garden Piloto N° 179 Iquitos 2022 focused on a quantitative, descriptive correlational investigation, in a non-experimental, transversal design in a sample population of 141 students focusing on a stratified probabilistic sampling, applying instruments focused on obtaining information through direct observation of the students, applying descriptive statistics, as well as The Pearson correlation test rxy = 0.700, it indicates a high positive relationship between both variables. 70.2% (99) of the children presented a level of basic social skills, 25.5 (36) of the children presented a level of social skills. advanced and 4.3% (6) of children's level of effective social skills respectively. They conclude the research stating that there is a significant relationship between the study variables, social skills and development of self-esteem, applying Kendall's Tau-b coefficient where its calculated value of 7.097 and approximate significance of 0.000 (p < 0.05), the normality of the variables social skills and development of self-esteem, obtaining significance of 0.000 in both variables (p-value < 0.05), so we reject the null hypothesis and accept the alternative hypotheses stating that both variables do not fit the normal distribution and has a free distribution, non-parametric tests such as Spearman's rho are carried out in the inferential analysis, which for its contrast uses the Student's t test statistic with n-2 degrees of freedom. It is also recommended that it should be efficiently apply the development of basic, affective and advanced social skills to improve the comprehensive development of self-esteem.